New elements of phenomenology of forced labour in Poland – recent cases (Biuletyn Kryminologiczny, 2013)
My presentation deals with the peculiarities of the forced labour in Poland, especially taking into account significant changes which has occurred recently. In order to understand the phenomenon of the forced labour and to reveal the specifics of human trafficking in Poland one should recall an important issue. Poland is not only a destination country for the victims of a forced labour and trafficking, but also a source and transit country for them. Therefore, Poland should be engaged in the numerous aspects of combating the forced labour and human trafficking.